The Effect of Shade, KNO3, Bulbil Conditions on The Shoot Emergence and Porang Growth - nurshanti, Dora fatma; Lakitan, Benyamin; Hasmeda, Mery; Ferlinahayati; Zaidan, Zaidan; Susilawati, Susilawati; Rofiqoh, Purnama Ria (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2025)
Porang cultivation can be carried out using three planting materials, namely true seeds, bulbils, and cormel, these three planting materials experience dormancy. Potassium Nitrate Solution (KNO3) is a chemical compound that is effective in breaking the dormancy of some plant seeds.This study aims to the effect of shading, soaking with KNO3 and bulbil conditions on the emergence of shoots and the growth of porang plants. The research was conducted in September 2021 to November 2021. The design used was split split plot using three factors, shading (N) as the main plot, namely N0: without shade, N1: 45%, N2: 55%, N3: 80%, KNO3 concentration (K) as subplots, namely K0: Without immersion KNO3, K1: 1500 ppm, K2: 3000 ppm, K3: 4500 ppm and bulbil conditions (D) as sub-sub plots, namely D0: Dormant and D1: Mentis. The data collected included the percentage of shoots emergence, time of shoot emergence, broken petiole sheath, leaf open fully, shoot height, number of shoots, number of leaves, petiole length, petiole diameter, midrib length, leaf width, leaf area and leaf thickness. The results showed that shading 55% and bulbil mentis accelerated the emergence of shoot at 26 DAP and 26.9 DAP, respectively. Soaking in KNO3 solution did not accelerate the emergence of shoots. The emergence of shoots affects the time of petiole sheath break and the leaves open fully, the faster the emergence of shoot, the faster the petiole sheath breaks, the faster the leaves open fully. Shade 80% increases the growth of porang plants with the longest leaf petiole of 22.6 cm; petiole diameter 5.5 mm; midrib length 10.34 cm; the width of the leaflets is 4.7 cm and the leaf area is 183.2 cm², except for the thickness of the leaves.